Simulation modeling of logistics processes provision based on the transport task - Kotov, Denys; Klymenko, Viktor; Androschuk, Oleksandr; Melnyk, Volodymyr; Goroshko, Oleksandr; Azyzov, Boris (Social Development and Security, 2024)
Purpose: the purpose of the article is to study the existing models of providing transport services and justify the feasibility of their application to solve the tasks of transport logistics in the military sphere. Method: the main method of research is the optimality method of applying the transport problem model for simulation modeling of logistics processes. Findings: the main theoretical aspects of the implementation of the optimality of the application of the model of the transport problem are formed in the work for the simulation modeling of logistics processes from the organization of movement, transportation (transportation) of material and technical means of the corresponding classes of supply by the units of the Logistics Forces from warehouses (supply centers) according to the defined logistics levels between consumers of the corresponding groups. Theoretical implications: the main results of the research on the topic of the article are: improvement of existing models of providing transport services by means of the optimality method of applying the model of the transport problem to carry out simulation modeling of logistics processes for the transportation of material and technical means by the units of the Logistics Forces. Paper type: theoretical.